Implementasi Prinsip Good Corporate Governance Pada Perbankan Syari’ah Di Indonesia - Muhamad Ridho; Muhamad Nurcholis; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
A bank is a financial institution that functions as a financial intermediary for two parties, namely those who have excess funds and those who are poor who lend funds. Shari'ah principles are provisions of agreements based on Islamic law between banks and other parties to deposit funds and/or finance business activities, or declare other activities according to shari'ah. ; transparency, accountability, responsibility, independence and fairness. GCG principles strongly support syar'i. In Islam there are also many muamalah principles such as; justice, tazawun, masuliyah, behavior, shiddiq, amanah, fathanah, tabligh hurriyah, alms, wasathan, ghirah, idarah, caliph, aqidah, ijabiyah, raqabah, qira'ah and islah. The implementation of the implementation of GCG in various institutions that carry out profit-oriented businesses, especially Islamic financial institutions/banks, is a certainty, even Islamic financial institutions, especially Islamic banks, must be pioneers, because to continue to run the principles Islamic terminology.